Implementation of SKB Number 229 of 2021, Number 154 of 2021, Number KB/2/VI/2021 against ITE Delik Article 27 Paragraph (3) of Law Number 11 of 2008 - Aguk Nugroho (Publikasi Indonesia, 2024)
Defamation through social media is regulated in Article 27 Paragraph (3) of Law Number 11 of 2008 concerning Electronic Information and Transactions as amended by Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions. In fact, the article seems to be a rubber article because it can easily be applied, especially to events that actually fall within the scope of ordinary disputes between individuals through social media or limited to reality stories that then make personal offenses that are considered an attack on honor / good name. This then became a polemic in itself in the community because of the application of articles that are multiinterpretive without paying attention to the scope of events. The problem examined in this study is how the criminal provisions according to Article 27 (3) of the ITE Law and the limitations of the application of article 27 paragraph (3) of the ITE Law. As a form of problem solving for the polemic that continues to occur, on June 23, 2021, the government issued a Joint Decree of Criteria Guidelines. Implementation of the Law on Information and Electronic Transactions (SKB UU ITE). This decree was signed by the Minister of Communication and Information, the Attorney General and the Chief of the National Police of the Republic of Indonesia, which is expected to be a law enforcement guideline so that there is no multiinterpretation of the implementation of the ITE Law which previously became a rubber article.